(NkAMNI RADOSTI (B:s [(No CWETNYH KAMNQH kOLXSKOGO POLUOSTROWA(B] /s - (NdAW(B, (NwLADIMIR nIKOLAEWI^s; (NpOZNQKOWA(B, (Ng(B.s ((NmURMANSK (B:s (NmURMANSKOE KN(B. (NIZD(B-(NWO(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 269-270s
Keywords: (NkOLXSKIJ POLUOSTROWs; (NcWETNYE KAMNIs